Preserving and promoting Malay folklores through souvenir product: Pak Belalang / Dinah Rakhim and Verly Veto Vermol - Rakhim, Dinah; Vermol, Verly Veto (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Malay legends and folklore are one of the heritage gems that unite us as people through many centuries. It is a tradition that has been passed down through many generations in oral and written among the people. It tells the story of our people and some address various messages to be learnt. Malay folklore should be preserved and passed down to future generations as it contributes to a greater understanding of national identity. Ignorance of the current generations and lack of concern in protecting our Malay folklore will result in future generations with less understanding of national roots which also result in a lack of identity. Articles by local researchers can be found on ways to attract a contemporary audience and preserving the folklore tradition. The researcher was given the task of promoting Malay folklore by designing a product souvenir for the tourism industry as it reflects the country's tradition to the world. It can be an interactive tool in remembering Malay folklore and also as an introduction to other countries about Malay folklore. One of the famous Malay folklore is Pak Belalang which has its adaptation of a movie directed by Tan Sri P Ramlee. It is a comedic story that attracts many families. This article will share in-depth the story of Pak Belalang and how it works as a tool in bringing back the national heritage through an effective souvenir that reflects the country's tradition and identity.